Trial of Utilization of Biogas from Palm Oil Mill Effluent on Household Gas Burner - Purwo Subekti; Defidelwina; Ikhsan Gunawan; Heffi Christya Rahayu; Pada Lumba; Yuliana Susanti; Laily Fitriana; Budi Irwansyah; Januar Kaswari (Fakultas Teknik Universitas Pasir Pengaraian, 2023)
The utilization of biogas produced from the liquid left over from palm oil mill enffluent (POME) needs to be increased, so far the use of biogas from POME for large-scale is new for the purpose of fueling power plant generators (PLTBg). Another increase in the use of biogas is among others as fuel for household-scale gas burner. The trial was carried out by utilizing biogas from the PLTBg purification unit and modifying commercial gas burner. Based on the results of trials, the flame produced is blue and can be used for cooking as the color of the fire from a stove that uses commercial gas. These results prove that apart from being PLTBg fuel, biogas from POME can be used as fuel for domestic purposes and possibly as fuel for other purposes.